Cryptosporidium parvum outbreak associated with Raccoons at a Wildlife Facility—Virginia, May–June 2019. (14th February 2022) - Davis, Meredith K.; Riley, Jennifer; Darby, Brandy; Murphy, Julia; Turner, Lauren; Segarra, Marta D.; Roellig, Dawn M.
Abstract: Cryptosporidium parvum is a parasitic zoonotic pathogen responsible for diarrheal illness in humans and animals worldwide. We report an investigation of a cryptosporidiosis outbreak in raccoons and wildlife rehabilitation workers at a Virginia facility. Fifteen (31%) of 49 facility personnel experienced symptoms meeting the case definition, including four laboratory‐confirmed cases. Seven juvenile raccoons were reported to have diarrhoea; six had laboratory‐confirmed cryptosporidiosis. Cryptosporidium parvum of the same molecular subtype (IIaA16G3R2) was identified in two human cases and six raccoons. Raccoon illness preceded human illness by 11 days, suggesting possible zoonotic transmission from raccoons to humans. This appears to be the first report of a human cryptosporidiosis outbreak associated with exposure to raccoons infected with C . parvum . Raccoons might be an under‐recognized reservoir for human C . parvum infections. Further study is needed to explore the prevalence of cryptosporidial species in raccoons and their role as a wildlife reservoir.